Executive functioning and spoken language skills in young children with hearing aids and cochlear implants: Longitudinal findings - Jamsek, Izabela A.; Kronenberger, William G.; Pisoni, David B.; Holt, Rachael Frush (Frontiers in Psychology, 2022)
Deaf or hard-of-hearing (DHH) children who use auditory-oral communication display considerable variability in spoken language and executive functioning outcomes. Furthermore, language and executive functioning skills are strongly associated with each other in DHH children, which may be relevant for explaining this variability in outcomes. However, longitudinal investigations of language and executive functioning during the important preschool period of development in DHH children are rare. This study examined the predictive, reciprocal associations between executive functioning and spoken language over a one-year period in samples of 53 DHH and 59 typically-hearing children between ages 3-8 years at baseline. Participants were assessed on measures of receptive spoken language (vocabulary, sentence comprehension, and following spoken directions) and caregiver-completed executive functioning child behavior checklists during two in-person home visits separated by 1 year. In the sample of DHH children, better executive functioning at baseline (Time 1) was associated with better performance on the higher-order language measures (sentence comprehension and following spoken directions) one year later (Time 2). In contrast, none of the Time 1 language measures were associated with better executive functioning in Time 2 in the DHH sample. Typically-hearing children showed no significant language-executive functioning correlations over the one-year study period. In regression analyses controlling for Time 1 language scores, Time 1 executive functioning predicted Time 2 language outcomes in the combined DHH and typically-hearing samples, and for vocabulary, that association was stronger in the DHH than in the typically-hearing sample. In contrast, after controlling for Time 1 executive functioning, none of the regression analyses predicting Time 2 executive functioning from Time 1 language were statistically significant. These results are the first findings to demonstrate that everyday parent-rated executive functioning behaviors predict basic (vocabulary) and higher-order (comprehension, following directions) spoken language development one year later in young (3-8 year old) DHH children, even after accounting for initial baseline language skills.